2009
DOI: 10.1002/pro.246
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward heterologous expression of active G‐protein‐coupled receptors in Saccharomyces cerevisiae: Linking cellular stress response with translocation and trafficking

Abstract: High-level expression of mammalian G-protein-coupled receptors (GPCRs) is a necessary step toward biophysical characterization and high-resolution structure determination. Even though many heterologous expression systems have been used to express mammalian GPCRs at high levels, many receptors are improperly trafficked or are inactive in these systems. En route to engineering a robust microbial host for GPCR expression, we have investigated the expression of 12 GPCRs in the yeast Saccharomyces cerevisiae, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 49 publications
8
79
0
Order By: Relevance
“…E. coli expression systems have been employed to produce heterogeneous preparations of neurotensin and olfactory receptors (Grisshammer, 2006(Grisshammer, , 2009White and Grisshammer, 2007;Song et al, 2009). Yeast Saccharomyces cerevisiae and Schizosaccharomyces pombe expression systems have been used to express large quantities of A 2a -adenosine receptor with ligand-binding characteristics near those of wild type (Niebauer et al, 2004;Niebauer and Robinson, 2006;O'Malley et al, 2009). Production through cell-free expression systems has proven useful for structural determinations of both soluble and membrane protein targets (Chen et al, 2007b), but large-scale use of these techniques for GPCR expression have yet to yield a GPCR structure (Klammt et al, 2007a,b;Junge et al, 2008Junge et al, , 2010.…”
Section: A G Protein-coupled Receptor Construct Design and Expressionmentioning
confidence: 99%
“…E. coli expression systems have been employed to produce heterogeneous preparations of neurotensin and olfactory receptors (Grisshammer, 2006(Grisshammer, , 2009White and Grisshammer, 2007;Song et al, 2009). Yeast Saccharomyces cerevisiae and Schizosaccharomyces pombe expression systems have been used to express large quantities of A 2a -adenosine receptor with ligand-binding characteristics near those of wild type (Niebauer et al, 2004;Niebauer and Robinson, 2006;O'Malley et al, 2009). Production through cell-free expression systems has proven useful for structural determinations of both soluble and membrane protein targets (Chen et al, 2007b), but large-scale use of these techniques for GPCR expression have yet to yield a GPCR structure (Klammt et al, 2007a,b;Junge et al, 2008Junge et al, , 2010.…”
Section: A G Protein-coupled Receptor Construct Design and Expressionmentioning
confidence: 99%
“…Membrane fractions were treated with 0.1 M Na 2 CO 3 at pH 11, 2 M urea, or 1% SDS. SDS (1%) typically releases integrally bound proteins from the membrane (40,41), while milder extraction conditions are more consistent with peripheral proteins. Only treatment with SDS could quantitatively release Cls447a and Cls613a from the membrane (see Fig.…”
Section: Figmentioning
confidence: 99%
“…Research from different groups raises our concern about the homogeneity of yeast-expressed material [8,[31][32][33] . Their results indicate that the expressed product is a mixture of functional and nonfunctional receptors, because during optimization the expression of the functional GPCR will dramatically increase but the overall expression level is somewhat constant.…”
Section: Yeastmentioning
confidence: 99%
“…O'MALLEY et al investigated 12 GPCRs expressed in S cerevisiae, and only the A 2A adenosine receptor retained its ligand binding activity. Other receptors, despite being processed and expressed in the same conditions, failed to localize in the plasma membrane and had no detectable ligand binding [31] . A more detailed study using N-terminal sequencing and N-glycosylation detection demonstrated that most of these nonfunctional receptors were not properly processed.…”
Section: Yeastmentioning
confidence: 99%